Layanan online Perpustakaan Perguruan Tinggi sebelum dan sesudah pandemi covid-19: Studi perpustakaan UIN Sunan Ampel sejak 2018 hingga 2020 - Samidah Nurmayuni (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2020)
The existence of the Covid-19 pandemic in early 2020 had many impacts on normal human activities, including the activities of the Sunan Ampel UIN Library.Offline or offline service activities are temporarily suspended, this is due to avoiding direct contact with users as a precautionary measure and transmission of Covid-19. The purpose of this study is to determine how much the level of user needs to visit the library website. The research method used in this research is literature study and action research method. Literature study is to see scientific concepts related to library science and action research methods to carry out research that is carried out continuously through reciprocal collaboration between librarians and users, until solutions to problems are found in the library. The data is processed and presented in numerical form and presented descriptively. The results of this study are that the need for online services is very important for users as an effective form of information communication. Information services related to information sources in supporting research for students and lecturers are still very much needed through subscriptions to journal databases and e-books, the UIN library can collaborate between other libraries. Library services are required to provide optimal online services, a change from manual services (offline) to digital services (online)